2013
DOI: 10.1016/s0034-7094(13)70197-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective Suprascapular and Axillary Nerve Block Provides Adequate Analgesia and Minimal Motor Block. Comparison with Interscalene Block

Abstract: Both techniques are safe, effective, and with the same degree of satisfaction and acceptability. The selective blockade of both nerves showed satisfactory analgesia, with the advantage of providing motor block restricted to the shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 17 publications
3
29
1
Order By: Relevance
“…Nonetheless, 2 RCTs (combined n = 129) set out to compare ISB and combined AXB-SSB in patients undergoing arthroscopic shoulder surgery (mainly rotator cuff repair) under general anesthesia. 55,56 The results of both trials confirmed Checcucci and colleagues' and Price's suspicion. Compared with ISB, AXB-SSB resulted in higher intraoperative opioid requirements, 56 increased pain/opioid consumption in the postanesthesia care unit, 55,56 and decreased patient satisfaction at 6 hours.…”
Section: Distal Nerve Blocks For Shoulder Surgerysupporting
confidence: 70%
See 1 more Smart Citation
“…Nonetheless, 2 RCTs (combined n = 129) set out to compare ISB and combined AXB-SSB in patients undergoing arthroscopic shoulder surgery (mainly rotator cuff repair) under general anesthesia. 55,56 The results of both trials confirmed Checcucci and colleagues' and Price's suspicion. Compared with ISB, AXB-SSB resulted in higher intraoperative opioid requirements, 56 increased pain/opioid consumption in the postanesthesia care unit, 55,56 and decreased patient satisfaction at 6 hours.…”
Section: Distal Nerve Blocks For Shoulder Surgerysupporting
confidence: 70%
“…55,56 The results of both trials confirmed Checcucci and colleagues' and Price's suspicion. Compared with ISB, AXB-SSB resulted in higher intraoperative opioid requirements, 56 increased pain/opioid consumption in the postanesthesia care unit, 55,56 and decreased patient satisfaction at 6 hours. 56 However, analgesic duration was longer, and pain scores were lower at 24 hours with AXB-SSB.…”
Section: Distal Nerve Blocks For Shoulder Surgerysupporting
confidence: 70%
“…These differences could be attributed to lower rate of incomplete SSN and AN blocks found in our study (18.7% and 25%, respectively) compared with Dhir and colleagues' trial 14 (39.3% and 41.4%, respectively). Pitombo and colleagues' 12 and Dhir and colleagues' 14 trials have also found SSB to be the more effective analgesic technique at 24 hours. However, our study does not support this conclusion because pain levels were similar at 24 hours in the 2 study groups, and opioid consumption was comparable between 12 and 24 hours.…”
Section: Discussionmentioning
confidence: 96%
“…Eligibility criteria in the current study were similar to those used by other trials that established efficacy of the reference treatment. [12][13][14] Using a computer-generated random allocation sequence (created by the study statistician), patients were randomly assigned to ultrasound-guided SSB (n = 50) or ISB (n = 50). Allocation numbers were sealed in opaque envelopes, which were opened in sequence by an independent anesthesiologist who was not involved in the assessment of outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The classic posterior approach to the nerve was first introduced in 1941 5. This approach to the SSN (in the supraspinatus fossa) proposed as an alternative analgesic block while preserving phrenic nerve function6 can be associated with higher technical failures 7. It has been modified multiple times, is technically challenging and has shown conflicting results 8.…”
Section: Introductionmentioning
confidence: 99%